Massive Open Online Courses: designing for the unknown learner. Issue 1 (2nd January 2016) - Macleod, Hamish; Sinclair, Christine; Haywood, Jeff; Woodgate, Amy
ABSTRACT: University teachers are faced with a problem of 'knowing' their learners when teaching on a Massive Open Online Course (MOOC). This paper explores and analyses what the University of Edinburgh has come to know about its recent MOOC participants, highlighting one particular course. We draw attention to barriers and enablers from co-existent understandings and expectations of course design, and from an abundance of highly qualified participants. We compare characteristics of participants who report a positive experience with those who do not. Mixed messages about teacher presence may have implications that go beyond MOOCs. We contemplate whether the participant group should be seen as a single massive multivocal entity. The paper concludes with a discussion of the potential opportunity for MOOCs to challenge standardization, homogenization and commodification of education. Shifting attention from the achievements of an individual to what can be done with a multitude, MOOCs may open up new educational arenas.